The importance of colloids and mires for the transport of uranium isotopes through the Kalix River watershed and Baltic Sea - Porcelli, D; Andersson, P; Wasserburg, G; Ingri, J; Baskaran, M (1997)
The importance of colloids and organic deposits for the transport of uranium isotopes from continental source regions and through the estuarine environment was investigated in the mire-rich Kalix River drainage basin in northern Sweden and the Baltic Sea. Ultrafiltration techniques were used to separate uranium and other elements associated with colloids > 10 kD and >3 kD from "solute" uranium and provided consistent results and high recovery rates for uranium as well as for other elements from large volume samples. Uranium concentrations in 0.45 μm-filtered Kalix River water samples increased by a factor of 3 from near the headwaters in the Caledonides to the river mouth while major cation concentrations were relatively constant. 234U/238U ratios were high (δ234U = 770-1500) throughout the basin, without showing any simple pattern, and required a supply of 234U-rich water. Throughout the Kalix River, a large fraction (30-90%) of the uranium is carried by >10 kD colloids, which is compatible with uranium complexation with humic acids. No isotopic differences were found between colloid-associated and solute uranium. Within the Baltic Sea, about half of the uranium is removed at low salinities. The proportion that is lost is equivalent to that of river-derived colloid-bound uranium, suggesting that while solute uranium behaves conservatively during estuarine mixing, colloid-bound uranium is lost due to rapid flocculation of colloidal material. The association of uranium with colloids therefore may be an important parameter in determining uranium estuarine behavior. Mire peats in the Kalix River highly concentrate uranium and are potentially a significant source of recoil 234U to the mirewaters and river waters. However, mirewater data clearly demonstrate that only small 234U/238U shifts are generated relative to inflowing groundwater. A simple box model of uranium accumulation in peat and transport through the mire that is compatible with the mire data demonstrates that with efficient removal of uranium from solution, only small shifts in 234U/238U ratios can be generated in mirewater uranium. The measurements and model calculations show that mirewaters are not the primary source of the uranium in the river. Bedrock groundwaters with high 234U/238U ratios and uranium concentrations must be the dominant source of riverine uranium. Copyright © 1997 Elsevier Science Ltd.